Efficient resource allocation of latency-aware slices for 5G networks - Ahmad, Muhammad Talat Fahim Sayyid; Ibrahim, Mayy Zaki; al-Shinnawi, Nada Muhammad (Journal of Engineering Research - Egypt, 2023)
It's noticed that 5G mobile networks are considered to be an emerging technology that serves multiple users with varying types of applications having different quality of service (QoS) needs. network slicing enables us to accommodate diverse services on the same infrastructure by using multiple virtual networks on the same physical infrastructure of the network. in this paper, a resource allocation framework to fairly share the network resources among different slices subject to delay sensitive requirements based on the priority factor of each slice to use the available radio resources efficiently is proposed. this priority factor depends on the weight of each slice and considering the quality of service of each one. the proposed framework ensures that each slice can share the high limits of allowable resources to achieve the least allowable latency as it is the most significant feature in 5G cellular networks. packet loss and packet scheduling delay are used as performance metrics when compared with other existing resource allocation algorithms. the simulation results validated that our framework could serve the delay-sensitive slices with the least allowable delay and guaranteed throughput.